Metabolic Properties of Alcohol Products (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Consumption of alcohol in large quantities leads to a significant increase in mortality. For example, a study found that people who consumed 5 or more units of alcohol on drinking days had a 30% higher mortality rate than those who consumed only one unit.